Leadership in School Social Work: Implications for Promoting the Preparedness of Tomorrow’s Practitioners - Yasmine Perry; Susan E Elswick; Matthew J Cuellar (International Journal of School Social Work, 2022)
Current research suggests that leadership skills in the field of school social work are valuable and needed. However, these skills are not always clearly outlined by governing entities as a result of little examination and research. This article examines differences of perceptions toward and engagement in professional leadership skills among school social work practitioners across the United States (N = 686). Using descriptive and multivariate methods, this paper examines practitioner perceptions toward and engagement in school-based leadership and what this leadership looks like in today’s schools. Findings call for educators and practitioners to advocate for the incorporation of leadership training, culturally sensitive cross-discipline collaboration, and preparedness guidelines in both generalist bachelor- and master-level social work curricula in which students are trained to work in school settings. Moreover, access to training and availability of resources pertaining to leadership appear to be a point of concern. Implications for social work practice, education, and research are discussed.
Keywords: School social work; professional leadership; survey research; mixed method